Sensibilização ambiental com crianças da educação infantil usando o peixe-boi-da-Amazônia (Trichechus Inunguis) - Silva, Fabrícia Souza da (2020)
Working with environmental awareness in Early Childhood Education is extremely important to train small citizens aware of their role with the environment. Therefore, it is relevant to work on our environment and the consequence of human action on it, so that in order for children at an early stage to realize that all the impact by human action will directly or indirectly interfere in the balance of the planet. Our objective is to understand how the environmental awareness process occurs in Early Childhood Education, considering its importance to arouse interest in children for preservation of endangered species of Amazonian fauna, using “Manatees” (Trichechus inunguis) as a facilitating element. Regarding the methodological procedures, this a qualitative research with a descriptive and participant approach. It was held in two Municipal Elementary schools and in the “Forest of Science” of the National Institute of Amazonian Research. Sixty-three (63) subjects participated in this study, sixty (60) small children and three (3) teachers. The data was collected with participant observation, recorded in the field notebook, through semi-structured interview with teachers, and didactic sequence elaborated and structured in accordance with environmental awareness workshops. We used Bardin's Content Analysis to analyze the data collected, from which we built environmental awareness indicators. Finally, we emphasize that environmental awareness practices are contained in the teachers' pedagogical planning; however, they are carried out only on specific dates of the SEMED school calendar, such as the Environment Week. It was possible to awaken in children the sensitivity for the preservation of endangered species of Amazonian fauna, by mean of workshops that we held in the educational spaces; this was evidenced in the environmental awareness indicators that were built from the children's speeches and attitudes.